Strategic Integration of Sustainable Accounting in Firms : A Case of East African Breweries Limited (EABL) - Catherine Mosiara Kenyatta; Dwi Suhartini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The East African Breweries Limited is one of the most notable beverage manufacturers in East Africa. This study aims to explore the company’s integration of sustainable accounting, especially given the paucity of information on how organizations incorporate the now popular environmental, social and governance (ESG) considerations. It is for this reason that this paper hopes to provide profound insight into the mater especially within the Kenyan corporate context. The author utilized a descriptive qualitative approach and used highly credible secondary sources, including sustainability reports, expert reviews, policy documents and recent scholarly materials. Thematic content analysis ensured the study identifies strategies used by companies currently, the most strategic integration frameworks and the impact of these mechanisms on stakeholder value and overall decision-making. Findings show that the organization has made significant inroads in implementing sustainability. Still, there are challenges that continue to face this process, including inadequate integration into the financial decision-making process and poor reporting. Undoubtedly, this paper valuable real-world recommendations for boosting integration of sustainability efforts into accounting and contributes to the current academic discourse on the significance of corporate sustainable accounting in East Africa.